Immunoexpression of P53 protein in trophoblastic diseases - Abdulhameed, Tenya T.; Shalal, Tara M.; Ahmedi, Nadya Y.; Ali, Sanarya M. (Zanco Journal of Medical Sciences (ZJMS), 2017)
Background and objective: Trophoblastic diseases constitute a spectrum of tumors and tumor- like conditions characterized by proliferation of pregnancy associated trophoblastic tissue of progressive malignant potential. This study aimed to assess the value of p53 protein immunoexpression in the diagnosis of hydatidiform molar pregnancy and the differential diagnosis of its subtypes (complete and partial) from abortions. Methods: A cross-sectional study of tissue sections from 68 formalin-fixed, paraffin- embedded specimens of products of conception, including 1st trimester abortion (n=15), partial hydatidiform mole PHM (n=24), complete hydatidiform CHM (n=24) and full term placenta (n=5), all were examined at the Histopathology Department of Maternity Teaching Hospital in Erbil, Iraq during the period of Jan.2013-Jun.2013. Immunohistochemistry was performed using p53 antibody and the standard streptavidin-biotin immunoperoxidase method. The labeling index (number of positive nuclei/total number of nuclei) for villous cytotrophoblasts, syncytiotrophoblasts and stromal cells were evaluated separately. Statistical analysis was carried out by one way ANOVA and Fisher’s exact tests, statistical significance was determined at P ≤0.05. Results: All villous trophoblastic lesions showed higher p53 immunoexpression in all villous components especially cytotrophoblasts, being the highest in complete hydatidiform mole (>50%) and partial hydatidiform mole (>20%). A statistically significant difference was found in immunoexpressins of p53 that was useful in separating abortion from complete hydatidiformmole, P <0.001, and partial hydatidiform mole, P <0.0002. It was also useful in separating between the complete hydatidiform mole and partial hydatidiform mole (P <0.001). Conclusion: p53 immunoexpression was valuable in differentiation between molar and non molar pregnancies and between subtypes of molar pregnancies.